The Development of Seabin Boat As a Waste Collector for Marine Pollution - Nawi, Adnin Afifi; Sarudin, Farisya Nabella; Zulfakri, Nurul Lisa; Mohamad Tajudin, Ahmad Zafran (Multidisciplinary Applied Research and Innovation, 2021)
70 percent of the surface of the earth is covered by the ocean and it is our responsibility to save it from pollution. Over the years, marine pollution has become a serious issue especially due to the mismanagement of plastic waste. In this project, a prototype of a seabin boat that could collect trash on the water surface was developed. The working performance of the boat in terms of buoyancy, stability, the speed of the boat, and energy supply were also tested. This project was started with the design of the prototype. Then the body of the prototype was set up by using styrofoam which is the main material for this project. Besides that, a table mat was used to act as a conveyer with the power of 9 V batteries and 6 V motors. The working performance of the boat in terms of buoyancy, stability, speed of the boat, and energy supply was tested in a pool in UTHM Pagoh. Archimede’s principle was also applied to do the testing. Based on the result obtained, the boat could perform well in terms of buoyancy, stability, speed, and energy supply. The boat could collect a 240 g load of weight with maximum speed, 0.043m/s, and energy capacity equals 500 mAh. Further research needs to be conducted to improve the performance of the prototype.